The role of sequence elements and protein interactions in focal subcellular localization of Sortase A in Enterococcus faecalis - Mitra, Sumitra Debina (2018)
Sortase A (SrtA) is a transmembrane protein responsible for covalently anchoring several virulence factors and adhesins to the cell wall of Gram-positive organisms, including Enterococci. In E. faecalis, SrtA localizes to single foci at the septum during early division phases and reorients to multiple foci at sites of nascent cell division during later stages of the cell cycle. Structurally, SrtA consists of an N-terminal positively charged cytoplasmic tail, a single transmembrane helix (TMH), and a C-terminal catalytic domain. In this thesis, we identify factors that govern the localization of SrtA in E. faecalis. We carried out alanine scan mutagenesis to identify important residues on the cytoplasmic tail and TMH region that are important for focal localization (fused to GST) and identified seven individual mutations that resulted in mislocalization of GST. While these amino acids, individually, did not perturb localization in full-length SrtA, the Asn residue at position 31 on the TMH showed a defect in SrtA substrate attachment to the cell wall. We also identified novel interacting partners of SrtA through crosslinking and co-immunoprecipitation. Mass spectrometry analysis revealed putative interacting proteins including chaperone proteins DnaK, GroEL, and HtrA; cell division protein DivIVA; signal recognition particle receptor FtsY; and cell wall machinery protein FtsI. We validated the interactions in vivo and identified DnaK and FtsY to be the strongest interacting partners of SrtA. We further demonstrate that in a DnaK mutant background, SrtA is mislocalized to one half of the cell in the mid-division growth phase suggesting that DnaK governs SrtA in a cell cycle dependent manner. Together these findings suggest that SrtA localization to distinct foci in E. faecalis may be governed, independently or in conjunction, by sequence elements and multiple protein-protein interactions at the septum of the cell.